Pooling the ground: understanding and coordination in collective sense making - Rączaszek-Leonardi, Joanna; Dębska, Agnieszka; Sochanowicz, Adam (Frontiers in Psychology, 2014)
Common ground is most often understood as the sum of mutually known beliefs, knowledge and suppositions among the participants in a conversation. It explains why participants do not mention things that should be obvious to both. In some accounts of communication, reaching a mutual understanding, i.e., broadening the common ground, is posed as the ultimate goal of linguistic interactions. Yet, congruent with the more pragmatic views of linguistic behavior, in which language is treated as social coordination, understanding each other is not the purpose (or not the sole purpose) of linguistic interactions. This purpose is seen as at least twofold (e.g. Fusaroli, Rączaszek-Leonardi & Tylén, 2014): to maintain the systemic character of a conversing dyad and to organize it into a functional synergy in the face of tasks posed for a dyadic system as a whole. It seems that the notion of common ground may not be sufficient to address this dual character of interaction. In situated communication, in which meaning is created in the very process of interaction, both common (sameness) and privileged (diversity) information must be pooled task-dependently and across participants. In this paper, we analyze the definitions of common and privileged ground and propose extensions that may facilitate a theoretical account of agents that coordinate via linguistic communication. To illustrate the usefulness of this augmented framework, we apply it to one of the recurrent issues in psycholinguistic research, namely the problem of perspective-taking in dialogue, and draw conclusions for the broader problem of audience design.